Implementation of Blended Learning Model in Improving Learning Outcomes of Listening - Aji, Wisnu Nugroho; Pebryawan, Krisna; Budiyono, Sri; Yuliantoro, Agus; Yuwono, Suhud Eko (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2023)
The application of the blended learning model in learning listening skills described to know the learning outcomes and student responses is the aim of this study. The equivalent type of time series quasi-experimental design is the design model used in this study. The samples of the study were twenty one students from the S1 Indonesian Language and Literature Education in the academic year of two thousand nineteen by a purposive sampling method. The outcomes showed that there was an increase in the average student learning outcomes at each level. The result is evidence of improved learning outcomes. From the results of stude nt responses as a whole, students feel enthusiastic due to the blended learning model application which makes them enjoy the process of the learning more. There are eighty-five percent of students enthusiastic due to the blended learning model application which makes them enjoy the process of the learning more, which makes students more motivated, their interest increases, and there is also an increase in students' learning awareness by the application of the blended learning model in listening skills.